2013
DOI: 10.1103/physreva.87.013414
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional current excitation in tunneling ionization of asymmetric molecules

Abstract: Asymmetric photocurrent produced by ionizing laser pulses in a gas is known to be a highly efficient source of terahertz radiation. We examine the possibility of exploiting the asymmetry of the medium itself, rather than the properties of the laser field acting on it, to facilitate the generation of directional photocurrents. We show that the magnitude of directional current and the efficiency of its excitation in tunneling ionization of asymmetric molecules can be significantly enhanced compared to the case o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 31 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…We measured the positions of the BBO crystal corresponding to a local minimum of the energy of terahertz radiation ("nonoptimal" phase shift), because they can be measured more accurately than the positions corresponding to the maximum. The nonoptimal phase shift is displaced from the opti mal phase shift by π/2 ± πN, where N is an integer [9,10,[19][20][21][22][23][24]. Constraints on the energies of laser pulses in the reported measurements are determined by the sensitivity of the system of detection of terahertz radi ation (at low energies) and by the available energy of laser pulses in this experiment (at high energies).…”
Section: Generation Of Terahertz Radiation At Optical Breakdown Of Airmentioning
confidence: 99%
See 1 more Smart Citation
“…We measured the positions of the BBO crystal corresponding to a local minimum of the energy of terahertz radiation ("nonoptimal" phase shift), because they can be measured more accurately than the positions corresponding to the maximum. The nonoptimal phase shift is displaced from the opti mal phase shift by π/2 ± πN, where N is an integer [9,10,[19][20][21][22][23][24]. Constraints on the energies of laser pulses in the reported measurements are determined by the sensitivity of the system of detection of terahertz radi ation (at low energies) and by the available energy of laser pulses in this experiment (at high energies).…”
Section: Generation Of Terahertz Radiation At Optical Breakdown Of Airmentioning
confidence: 99%
“…DOI: 10.1134/S0021364015020095 different values of the optimal phase delay between laser radiation at frequencies ω and 2ω [15,16,[19][20][21][22] were obtained. Advanced approaches to the descrip tion of generation of directional currents with allow ance for the Coulomb interaction between a separated electron and the core of an atom or a molecule were proposed in [21][22][23][24]. These approaches make it possi ble to go beyond the strong field approximation and to perform simulation in a wide range of intensities of optical pulses.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] The essence of this phenomenon can be explained as follows. In the process of ionization of atoms and molecules by an intense laser field, the newly born free electrons acquire, along with oscillatory velocity, the constant drift velocity.…”
Section: Introductionmentioning
confidence: 99%
“…5,6 These approaches were used to calculate RCD dependences on CEP, intensity, and duration of the laser pulse. [2][3][4][5][6]8,9 It was shown that the efficiency of RCD excitation depends on the peak intensity of the pulse, and there exists an optimal intensity, whose value depends on the duration of the laser pulse. The RCD value, which corresponds to this optimal intensity, increases exponentially as the duration of the laser pulse decreases, which can be used for generation of high-power THz radiation employing very short laser pulses.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation